(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Recent armed conflicts in the Middle East and other regions demonstrate that nearly 80% of modern military engagements occur in urban areas, where the enemy often hides among civilians and uses high-rise buildings as defensive strongholds. These circumstances make high-altitude assault training a crucial element in preparing elite military units to operate effectively in dense, multi-story environments while minimizing civilian casualties. This article examines the tactical significance, methods, and practical applications of high-altitude assault training for special-purpose units. Emphasis is placed on reconnaissance and maneuvering in urban infrastructure, covert movement, room entry techniques, casualty evacuation, and the use of specialized alpine equipment. Vertical descent methods, including both positive and negative techniques, as well as emergency descent options without standard devices, are analyzed. The article further outlines the knowledge, skills, and competencies required for fighters to conduct high-risk operations in urban warfare. Drawing on national and international military experiences, the study underscores the vital role of high-altitude assault training in enhancing operational efficiency, safety, and mission success in modern combat scenarios.